The Role of P5 Activities in Forming the Character of Students - Eka Muliana, I Kadek; Putrayasa, I.B.; Martha, I.N. (Jurnal Multidisiplin Indonesia, 2022)
The application of the project to strengthen the Pancasila student profile (P5) in learning activities is an effort made to shape the character of students. The important thing contained in the implementation of this activity is its aim in strengthening the noble values of Pancasila in students. This study aims to determine the profile of Pancasila students in their role in shaping the character of students. The method applied in this research is the literature study method, that the series of data collection processes to processing data is based on existing literature. The results of this study indicate that the profile of Pancasila students is a government policy in supporting student character strengthening programs. The application of P5 is a learning effort in preparing the character and competence of students in dealing with all situations they face now and later at the next level of life. In general, the implementation of the P5 project is in the form of intra-curricular activities combined with extra-curricular and co-curricular activities which are able to provide opportunities for students to train and develop the values of responsibility, cooperation, problem solving and creativity, and leadership which is the result of the development of the dimensions of the Pancasila student profile and national character values